Energy and Industrial Growth in India: The Next Emissions Superpower?. (May 2017) - Pappas, Dimitrios; Chalvatzis, Konstantinos J.
Abstract: India is often referred to as the next development superpower and is widely seen as a potential destination for large scale manufacturing hubs. In this work we draw comparisons between India, Indonesia and China and find that all countries have a carbon intensive energy sector. However, there is a staggering difference between industrial energy intensity between them where India and Indonesia require double the amount of energy to produce the same output as China. We look into the decomposed industrial sectors and find that iron and steel and non-metallic minerals present the highest energy intensity in India. We argue that a production transition from China to India and Indonesia would result in a dangerous global emissions growth which has to be countered with rapid adoption of innovative energy technologies and policies.